Circulating let-7g-5p and miR-191-5p Are Independent Predictors of Chronic Kidney Disease in Hypertensive Patients. (2nd March 2020) - Berillo, Olga; Huo, Ku-Geng; Fraulob-Aquino, Júlio C; Richer, Chantal; Briet, Marie; Boutouyrie, Pierre; Lipman, Mark L; Sinnett, Daniel; Paradis, Pierre; Schiffrin, Ernesto L
Abstract: BACKGROUND: Hypertension (HTN) is associated with target organ damage such as cardiac, vascular, and kidney injury. Several studies have investigated circulating microRNAs (miRNAs) as biomarkers of cardiovascular disease, but few have examined them as biomarker of target organ damage in HTN. We aimed to identify circulating miRNAs that could serve as biomarkers of HTN-induced target organ damage using an unbiased approach. METHODS AND RESULTS: Fifteen normotensive subjects, 16 patients with HTN, 15 with HTN associated with other features of the metabolic syndrome (MetS), and 16 with HTN or chronic kidney disease (CKD) were studied. Circulating RNA extracted from platelet-poor plasma was used for small RNA sequencing. Differentially expressed (DE) genes were identified with a threshold of false discovery rate <0.1. DE miRNAs were identified uniquely associated with HTN, MetS, or CKD. However, only 2 downregulated DE miRNAs (let-7g-5p and miR-191-5p) could be validated by reverse transcription-quantitative PCR. Let-7g-5p was associated with large vessel stiffening, miR-191-5p with MetS, and both miRNAs with estimated glomerular filtration rate (eGFR) and neutrophil and lymphocyte fraction or number and neutrophil-to-lymphocyte ratio. Using the whole population, stepwise multiple linear regression generated a model showing that let-7g-5p, miR-191-5p, and urinary albumin/creatinine ratio predicted eGFR with an adjusted R 2 of 0.46 ( P = 8.5e −7 ). CONCLUSIONS: We identified decreased circulating let-7g-5p and miR-191-5p as independent biomarkers of CKD among patients with HTN, which could have pathophysiological and therapeutic implications.